Measuring the boxing punch: development and calibration of a non-embedded in-glove piezo-resistive sensor - Jovanovski, A.; Stappenbelt, B. (Proceedings, 2020)
Biomechanics measurement in boxing is becoming increasingly important for the analysis of boxing technique in order to promote exciting and safer boxing at both amateur and professional levels. Despite this interest, there have been few experiments within this field of research that have utilised a non-embedded in-glove sensor to measure the resultant power generated by a boxing punch. The aim of this study was to develop a dynamic measurement system, utilising a non-embedded in-glove sensor system. Two sensors were utilised; a tri-axial accelerometer to measure acceleration and a piezo-resistive force sensor hand wrap to measure the impact force of a boxer`s punch. The piezo-resistive system was calibrated using a static measurement system utilising simple load cells for force and laser displacement sensors for glove speed measurements. The system was tested on 31 novice boxing athletes participating in the study. A mean impact force of 2.31 kN ± 3.28 kN, an instantaneous velocity prior to impact of 4.73 m/s ± 0.35 m/s, an impact acceleration of 91 g ± 11 g, deceleration immediately following impact of 223 g ± 21 g and a maximum power dissipation of 11.2 kW ± 2.05 kW were measured. These values correspond well with prior studies using alternate measurement approaches. The calibration of the non-embedded in-glove piezo-resistive force sensor on the static measurement system yielded a correlation coefficient of 0.85.